2014
DOI: 10.1371/journal.ppat.1004324
|View full text |Cite
|
Sign up to set email alerts
|

RC1339/APRc from Rickettsia conorii Is a Novel Aspartic Protease with Properties of Retropepsin-Like Enzymes

Abstract: Members of the species Rickettsia are obligate intracellular, gram-negative, arthropod-borne pathogens of humans and other mammals. The life-threatening character of diseases caused by many Rickettsia species and the lack of reliable protective vaccine against rickettsioses strengthens the importance of identifying new protein factors for the potential development of innovative therapeutic tools. Herein, we report the identification and characterization of a novel membrane-embedded retropepsin-like homologue, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 77 publications
(98 reference statements)
1
30
0
Order By: Relevance
“…Firstly, we characterized the protease properties of Amuc_1434*. As Amuc_1434* contains the conserved "DTG" and "LLG" sequence motifs of the aspartic protease family [45], we measured its protease activity using hemoglobin as the substrate. We found that this enzyme could efficiently hydrolyze hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, we characterized the protease properties of Amuc_1434*. As Amuc_1434* contains the conserved "DTG" and "LLG" sequence motifs of the aspartic protease family [45], we measured its protease activity using hemoglobin as the substrate. We found that this enzyme could efficiently hydrolyze hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the sequence of Amuc_1434* contains the conserved "DTG" and "LLG" motifs of the aspartic protease family [45], it is perhaps not suprising that Amuc_1434* has the aspartic protease activity. Thus, we measured its protease activity using hemoglobin as the substrate.…”
Section: Amuc_1434* Activity Test and Kinetic Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Ratio of milk clotting to proteolytic activity is comparable with commercial fungal protease but has high thermostability Bacillus licheniformis Shows typical milk-clotting kinetics therapeutic intervention. is implies that a retropepsin type of aspartic protease enzymes is found in prokaryotes, signifying that these enzymes may represent an ancestral form of these proteases [16]. Acid protease produced by Bacillus subtilis, which is GRAS (genetically regarded as safe), is gradually replacing chymosin in cheese making, and protease produced from B. subtilis var.…”
Section: Bacillus Subtilismentioning
confidence: 99%
“…Thus, the proposed IS proves to be able to reduce the variability among 183 replicates while maintaining the ratios between experimental conditions. Most importantly, the use of 184 the IS not only proved to be beneficial in comparison to the total intensity but also when compared 185 with a set of other 11 popular normalization methods ( Figure 2b), which are able to largely decrease 186 the variability between replicates (Supplementary Figure 5 Rickettsia conorii [17], and NusA-3C-PSI which is a fusion of NusA protein from E. coli with the saposin-203 like domain of a plant aspartic protease; Supplementary Figure 6) were added in known amounts to 204 the secretomes immediately after medium collection to be used in targeted protein quantification in 205 this analysis. These two recombinant proteins were added in low amounts ( Supplementary Table 4), 206 only enough to be quantified and to reflect the usual levels of the proteins analyzed.…”
Section: Evaluation Of the Normalization Capacity Of The Is 152mentioning
confidence: 99%